Multi-input DC-DC converter for hybrid renewable energy generation system - Rosli, M.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper proposes a development of a Multi-input DC-DC Converter (MIDC) for Hybrid Renewable Energy Generation System (HREGS). The aim is to reduce the number of power converter and cost. The proposed MIDC consists of a DC-DC converter and a single phase full bridge DC-AC inverter. The renewable energy (RE) sources such as photovoltaic (PV) array, wind turbine (WT), hydrogen fuel cell (HFC) and battery bank (BT) are selected as the input power sources to the system. The Maximum Power Point Tracking (MPPT) is also used to operate PV array and WT sources at its maximum power by using the simple Perturbation and Observation (P&O) algorithm. The optimum power of HFC is controlled by Proton Exchange Membrane Fuel Cell (PEMFC). The proposed MIDC has been simulated by NI Multisim 12.0 software and its operations discussed thoroughly. Â© 2014 IEEE.